Evaluation of Potential Antigen-specific Host Biomarkers in QuantiFERON Supernatants as Candidates for the Diagnosis of Ocular Tuberculosis. (17th November 2021) - Makhoba, Nonjabulo S.; Smit, Derrick P.; Walzl, Gerhard; Chegou, Novel N.
ABSTRACT: Purpose : To evaluate potential host biomarkers detectable in QuantiFERON supernatants as diagnostic candidates for ocular tuberculosis (OTB). Methods : We investigated 47 host markers in QuantiFERON supernatants from 92 individuals with uveitis using the Luminex platform. We evaluated the potential of individual and combined biomarkers to distinguish between patients with possible, probable, and no OTB. Results : Differences were observed in median concentrations of several biomarkers including IL-13, IFN-γ, IFN-α2, and IL-1β, in individuals with OTB versus no OTB regardless of HIV status. Individuals with probable and possible OTB only differed regarding GM-CSF. We identified a four-marker biosignature (CD40 L, IL-33, IFN-γ, and SAP) which diagnosed OTB with an area under the ROC curve of 0.80, sensitivity = 56.3% and specificity = 90.0%. Conclusion : This represents the first attempt at screening QuantiFERON supernatants for biomarkers to diagnose OTB. We identified candidate biosignatures which may aid in diagnosing OTB in both HIV positive and negative patients.